Transcriptome‐wide sequencing provides insights into geocarpy in peanut (Arachis hypogaea L.). Issue 5 (26th October 2015) - Chen, Xiaoping; Yang, Qingli; Li, Haifen; Li, Heying; Hong, Yanbin; Pan, Lijuan; Chen, Na; Zhu, Fanghe; Chi, Xiaoyuan; Zhu, Wei; Chen, Mingna; Liu, Haiyan; et al.
Summary: A characteristic feature of peanut is the subterranean fructification, geocarpy, in which the gynophore ('peg'), a specialized organ that transitions from upward growth habit to downward outgrowth upon fertilization, drives the developing pod into the soil for subsequent development underground. As a step towards understanding this phenomenon, we explore the developmental dynamics of the peanut pod transcriptome at 11 successive stages. We identified 110 217 transcripts across developmental stages and quantified their abundance along a pod developmental gradient in pod wall. We found that the majority of transcripts were differentially expressed along the developmental gradient as well as identified temporal programs of gene expression, including hundreds of transcription factors. Thought to be an adaptation to particularly harsh subterranean environments, both up‐ and down‐regulated gene sets in pod wall were enriched for response to a broad array of stimuli, like gravity, light and subterranean environmental factors. We also identified hundreds of transcripts associated with gravitropism and photomorphogenesis, which may be involved in the geocarpy. Collectively, this study forms a transcriptional baseline for geocarpy in peanut as well as provides a considerable body of evidence that transcriptional regulation in peanut aerial and subterranean fruits is complex.